Design of Train Information Terminal Unit SimulationSoftware for CRH2 Train Network Simulation Platform - ZHAO Min; LIU Wang-hui; NI Wen-bo; WANG Xue-mei; CHEN Fa-qi (机车电传动)
After analyzing the terminal unit’s major functions in the CRH2 train network and its simulation software’s functionalrequirements in the simulation platform, the terminal unit simulation software was designed by using the MFC and ActiveX technology inVisual C++ 6.0 and WinPcap network program technology, which could simulate the terminal unit’s function of passing train controlinstructions, monitoring device working states, providing feedback on device state, and modeling device malfunctions. By simulating trainnetwork control system’s data exchange character, foundation for studying train network’s data exchange models and network performanceswas laid.